2011
DOI: 10.1002/cphc.201000904
|View full text |Cite
|
Sign up to set email alerts
|

Note on “The Electrochemical Promotion of Ethylene Oxidation at a Pt/YSZ Catalyst”

Abstract: Can a single oxygen spillover species on Pt explain the effect of electrochemical promotion of catalysis (EPOC or NEMCA, non-Faradaic electrochemical modification of catalytic activity, effect) with O 2À conductors such as YSZ (yttria-stabilized ZrO 2 ), as suggested in a recent paper published in this journal by Toghan, Rçsken and Imbihl, [1] or is it necessary to use the longtested sacrificial promoter mechanism, [2][3][4][5] which involves two oxygen species or-equivalently-two different oxygen adsorption s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…One main motivation for this study has been the possibility that at high pressure an oxygen spillover species might develop which is different from chemisorbed oxygen. The existence of such a special spillover species has been postulated by Vayenas and co-workers in order to explain the non-Faradaic nature of the EPOC effect but so far no valid experimental proof exists [4,5,9]. Also here no indication for the existence of O species with  close to 2 was found.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…One main motivation for this study has been the possibility that at high pressure an oxygen spillover species might develop which is different from chemisorbed oxygen. The existence of such a special spillover species has been postulated by Vayenas and co-workers in order to explain the non-Faradaic nature of the EPOC effect but so far no valid experimental proof exists [4,5,9]. Also here no indication for the existence of O species with  close to 2 was found.…”
Section: Discussionmentioning
confidence: 84%
“…A second issue discussed controversely in the literature is the origin of the non-Faradaic behavior in EPOC experiments. A "sacrificial promoter mechanism" based on the existence of a special spillover oxygen species was postulated by Vayenas et al [3,4] Alternatively, an ignition mechanism has been proposed by Toghan et al [9,11,12]. The ignition mechanism does not require a special oxygen spillover species and instead assigns the spillover species the role of triggering the reactive removal of an inhibitory adlayer.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important when carrying out NEMCA experiments under high vacuum. 234,359,360 4.9.2. Scale-Up: Multipellet, Multiplate, and Bipolar EPOC Reactors.…”
Section: Epoc Reactorsmentioning
confidence: 99%
“…One should therefore leave the possibility open that in the future some further experiments will be able to demonstrate that at high coverage/high pressure such a special spillover species exists or not. So far there is a quite agreement as the identity of chemisorbed oxygen and the spillover species at low coverage/low pressure is accepted by Vayenas and Imbihl, i. e. under these conditions only one oxygen species exists [81,92].…”
Section: Re −mentioning
confidence: 95%
“…responsible for the non-Faradaic rate increase [89][90][91]. A third possibility has been introduced recently by Toghan et al who suggested that ignition mechanism [48,49,[57][58][59]92]. The ignition mechanism does not require a special oxygen spillover species and instead assigns the spillover species the role of triggering the reactive removal of an inhibitory adlayer.…”
Section: Re −mentioning
confidence: 99%